A ftp application layer gateway prototype - Wong, Yoke Keong. (2010)
With the imminent depletion of global IPv4 address, there is greater urgency to transit computer systems from IPv4-based infrastructure to IPv6-based infrastructure. However, the effort of IPv6 transition has been hampered since not all vendors have IPv6 solutions yet and organizations cannot transit their network infrastructures without first having IPv6 solutions for all the components in their networks. An alternative to this would be providing transition solutions that allow communication between IPv6 and IPv4 networks. The current IPv6 transition strategies include dual stack implementation of all required equipment, tunneling mechanisms and IPv6 to IPv4 translators. One of the tools that satisfy the need of communication between IPv6 and IPv4 networks at lower added cost is the Stateless IPv4 to IPv6 translator. However a shortcoming of such translators is that it cannot support some applications as it is only doing a one-to-one mapping of address. One example of such supplication is the File Transfer Protocol (FTP). FTP is still widely used in organizations and for website management. Therefore there is a need to implement a FTP Application Layer Gateway (ALG) for FTP to work during IPv6 transition. The scope of this project is to implement a FTP ALG prototype to demonstrate is feasibility. The FTP ALG prototype is implemented by porting an existing FTP proxy to IPv6 and extending its functionality to support FTP operation over IPv6. The end result of the project is the successful implementation of a FTP ALG prototype that allows an IPv6 FTP client to communicate with an IPv4 FTP server. The case of IPv4 FTP client communicating with an IPv6 FTP server is also possible. In addition, the difference of the transfer time delay of a FTP connection involving the FTP ALG compared to the transfer time delay of a direct FTP connection is less than 10% for file sizes above 1500MB. In addition, the FTP ALG can run in parallel with other translator mechanisms like the IVI. Thus this allows greater flexibility in deploying the FTP ALG.